XOTEARTE, THE REALIZATION OF THE INSEPARABLE RELATIONSHIP BETWEEN CULTURE AND THE BODY (Editora Impacto Científico, 2025)
This work is a journey through the culture of forró. It explores forró not only as music and dance, but also as a living cultural heritage that integrates the body, mind, and community. The central objective of the work is to demonstrate how forró, in its multiple rhythms, articulates tradition, corporeality, and well-being, highlighting its social, symbolic, and therapeutic relevance. The research adopts a qualitative methodology, with an exploratory and descriptive character, combining cultural analysis and observation in developed activities. The results show that the regular practice of the dance strengthens social bonds, improves indicators of physical and mental health, promotes community belonging, and contributes to the appreciation of Northeastern traditions. The Xotearte Project demonstrates, in practice, that forró can act as an instrument of integral care, integrating body, culture, and health in collective and formative experiences. It is concluded that the appreciation of forró represents not only the preservation of a cultural heritage, but also an effective strategy for promoting quality of life and strengthening identity.DOI: https://doi.org/10.56238/edimpacto2025.090-061